Bank Uncertainty Regarding Inventory Collateral in Indonesian MSMEs Loans - Prasastinah Usanti, Trisadini; Sulani, Sulani (Kyiv-Mohyla Law and Politics Journal, 2024)
Purpose: An obligation in providing easy access to funding for MSMEs creates a dilemma for banks when the collateral is in the form of inventory objects. When MSMEs provide collateral in the form of inventory objects, it can cause uncertainty for banks as collateral recipients. This research examines legal protection efforts for banks when MSME credit guarantees are in the form of inventory objects. Methodology: The research method is normative juridical with analytical descriptive research, statute, conceptual, and case approaches. Results: The results showed that the existence of a norm in Law 42/1999, which allows fiduciary providers to sell inventories to third parties, results in legal uncertainty and risks to the bank's position as a preferred creditor. The fiduciary giver does not exchange inventory items that have been sold or traded but at a lower value. It is very detrimental to the bank if it is accompanied by an event of default from the debtor. The bank cannot sell the collateral object considering that the fiduciary giver has transferred the collateral object. Conclusion: Therefore, efforts are needed that can be made by banks to minimize these risks by asking for a personal guarantee (borg) as support for MSME credit.